The Internet of the Future 15th Open European Summer School and IFIP TC6.6 Workshop, EUNICE 2009, Barcelona, Spain, September 7-9, 2009, Proceedings - Oliver, Miquel; Sallent, Sebastià (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2009)
This volume presents carefully revised texts of selected lectures given at the 15th EUNICE Open European Summer School and the proceedings of the conjoint IFIP TC6.6 Workshop on Dependable and Adaptable Networks and Services, EUNICE 2009, held at Barcelona, Spain, in September 2009. The 23 revised full papers together with 11 posters presented were carefully reviewed and selected from 60 submissions. The papers are organized in topical sections on traffic engineering for the internet, P2P and multimedia, advanced applications for next generation networks, future internet architectures and models, pervasive wireless networks and protocols, innovative algorithms for network-related problems, disruptive technologies for future services and traffic analysis.